Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I got this interpretation:

If we have $y'(t)=u(t)$ , it's like have $y(t)=\int{u(t)dt} $

If we solve this simple equation, we obtain:

$$sY(s)=U(s)$$ $$Y(s)=\frac{U(s)}{s}$$

So, we have the $U(s)$ multiplied for $\frac{1}{s}$

Is this conjunction correct? It doesn't seem quite complete. What do you think?

share|improve this question
    
If you take Laplace transform of the ode with the initial condition $y(0)=0$, then your derivation is correct. –  Mhenni Benghorbal Sep 28 '13 at 14:14

2 Answers 2

up vote 1 down vote accepted

Assuming the initial condition to be $y(0)=0$, your formulation is correct. My only suggestion would be that you should adjust your terminology a bit. The Laplace transform of the integral isn't $\frac{1}{s}$. It'd be more accurate to say

The Laplace transform of an integral is equal to the Laplace transform of the integrand multiplied by $\frac{1}{s}$.

share|improve this answer

Laplace transform of f(t) is defined as $\text{F(s)=}\int _0^{+\infty }f(t)e^{-\text{st}}dt$

Thus, the Laplace transform of $\frac{df}{dt}$ can be derived as below.

$$ \int _0^{+\infty }\left(\frac{d}{dt}f(t)\right)e^{-\text{st}}dt=\int_0^{+\infty } e^{-\text{st}} \, df=f(t)e^{-\text{st}}|_0^{+\infty }+\int _0^{+\infty }f(t)\text{se}^{-\text{st}}dt $$ Note that $\text{$\exists $ F(s)=} \int _0^{+\infty }f(t)e^{-\text{st}}dt\Rightarrow f(t)e^{-\text{st}}|_{t=+\infty }=0$, we have $$ \int _0^{+\infty }\left(\frac{d}{dt}f(t)\right)e^{-\text{st}}dt=\text{sF}(s)-f(0) $$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.